Internal Tides Drive Nutrient Fluxes Into the Deep Chlorophyll Maximum Over Mid‐ocean Ridges. Issue 8 (14th August 2019) - Tuerena, Robyn E.; Williams, Richard G.; Mahaffey, Claire; Vic, Clément; Green, J. A. Mattias; Naveira‐Garabato, Alberto; Forryan, Alexander; Sharples, Jonathan
Abstract: Diapycnal mixing of nutrients from the thermocline to the surface sunlit ocean is thought to be relatively weak in the world's subtropical gyres as energy inputs from winds are generally low. The interaction of internal tides with rough topography enhances diapycnal mixing, yet the role of tidally induced diapycnal mixing in sustaining nutrient supply to the surface subtropical ocean remains relatively unexplored. During a field campaign in the North Atlantic subtropical gyre, we tested whether tidal interactions with topography enhance diapycnal nitrate fluxes in the upper ocean. We measured an order of magnitude increase in diapycnal nitrate fluxes to the deep chlorophyll maximum (DCM) over the Mid‐Atlantic Ridge compared to the adjacent deep ocean. Internal tides drive this enhancement, with diapycnal nitrate supply to the DCM increasing by a factor of 8 between neap and spring tides. Using a global tidal dissipation database, we find that this spring‐neap enhancement in diapycnal nitrate fluxes is widespread over ridges and seamounts. Mid‐ocean ridges therefore play an important role in sustaining the nutrient supply to the DCM, and these findings may have important implications in a warming global ocean. Plain Language Summary: The subtropical gyres cover an extensive area of the global ocean and account for ~30% of carbon export to the deep ocean. The pattern of the winds induces downwelling in these gyres and leads to surface waters being relatively nutrient impoverished. Biological production in the subtropical gyres is primarily limited by the availability of nitrate, which can be increased through mixing in the underlying thermocline. Internal tides can enhance mixing in the ocean interior close to steep sloping topography; deep in the ocean interior, this mixing is a key component of ocean physics. In our field study, we reveal the mixing extending up toward the surface and measured a tenfold increase in nitrate fluxes to phytoplankton in the surface ocean over the Mid‐Atlantic Ridge compared to in the surface waters in the adjacent deeper ocean. Importantly, nitrate fluxes over the ridge varied fortnightly with an eightfold increase from neap to spring tides. These inferences of enhanced mixing and nutrient supply along ridges and seamounts are relevant for the rest of the global ocean given the ubiquitous nature of the tides. Key Points: Internal tides provide a tenfold increase in diapycnal nitrate fluxes to the deep chlorophyll maximum over the Mid‐Atlantic Ridge Diapycnal nitrate fluxes increase by a factor of 8 between neap and spring tides Global tidal modeling experiments reveal that spring‐neap enhancement in diapycnal nitrate fluxes is widespread over ridges and seamounts